Réponses

Meilleure réponse !
2014-05-09T23:53:02+02:00
Bonsoir,

x.(4x - 7).(9 - 2x).[8 - (2/7).x] = 0

"Equation produit nul"

x = 0\ \ ou\ \ 4x - 7 = 0\ \ ou\ \ 9 - 2x = 0\ \ ou\ \ 8 - \dfrac{2}{7}x = 0\\\\x = 0\ \ ou\ \ 4x = 7\ \ ou\ \  - 2x = -9\ \ ou\ \  - \dfrac{2}{7}x = -8\\\\x = 0\ \ ou\ \ 4x = 7\ \ ou\ \  2x = 9\ \ ou\ \  \dfrac{2}{7}x = 8\\\\x = 0\ \ ou\ \ x = \dfrac{7}{4}\ \ ou\ \  x = \dfrac{9}{2}\ \ ou\ \  x = 8\times\dfrac{7}{2}\\\\x = 0\ \ ou\ \ x = \dfrac{7}{4}\ \ ou\ \  x = \dfrac{9}{2}\ \ ou\ \  x = 28\\\\\\ \boxed{S=\{0;\dfrac{7}{4};\dfrac{9}{2};28\}}